The main methods of examination of patients in clinic internal diseases : manual for the third-year students of the international faculty - Syvolap, V. V.; Oleynik, A. I.; Likhasenko, I. V.; Avramenko, N. F.; Gerasco, M. P.; Kurylez, L. O.; Zhemanyuk, S. P.; Сиволап, Віталій Вікторович; Олiйник, Олександр Iванович; Лихасенко, Іветта Валеріївна; Авраменко, Наталя Федорівна; Герасько, Марина Петрівна; et al. (Запорізький державний медичний університет, 2017)
The textbook is devoted to the discipline definition, the problems of diagnosis, and fundamentals of diagnostic process: history taking, inspection, and physical examination of the respiratory, cardiovascular, digestive systems.